PENGARUH GEL EKSTRAK DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav) TERHADAP PENYEMBUHAN LUKA BAKAR PADA KELINCI (Oryctolagus cuniculus) - Fina Ulviani; Yusriadi Yusriadi; Khildah Khaerati (Universitas Tadulako, 2016)
Research on Gel Formulation of red betel leaf extract (Piper crocatum Ruiz & Pav) for the treatment of burn wounds in rabbits (Oryctolagus cuniculus) has been conducted. This study aimed to determine variation’s effect of concentration in gel of red betel leaf extract for the treatment of burn wounds in rabbits which had been wounded using hot metal. In this study, the viscous extract was formulated into gel with concentrations of 1%, 2% and 3%. The Gel’s Physical quality evaluation included organoleptic, pH, homogeneity and dispersive ability tests on day 0 until day 28. The gel activity test was performed on 5 rabbits divided into five treatment groups. Each rabbit was burn-wounded using hot metal plate at diameter of 20 mm. Each group was given five wounds consisting of a negative control, 1%, 2%, 3% of extract formula and a positive control. The diameter measurement of the wounds was done on the 1st, 3rd, 5th, 7th, 9th and the 21st day. Data of wound healing percentage was statistically analyzed with Two-Way ANOVA. The results showed that the gel with 3% of red betel leaf extract of which percentage of healing as much as 85.81% compared to gel extract 1% and 2% with percentage 65,32% dan 76,58%.